Berkreasi Bersama Pembuatan Media Kantong Berhitung Berbasis Teori Bruner Bagi Guru Sekolah Dasar - Fitri, Ayu; Suparman, Tarpan; Asmara, Andes Safarandes; Fajar, Muhammad Jelang (IPI Press, 2024)
Improvements in information technology have created several innovative digital learning media. However, teachers often face obstacles in creating or using this media due to limited technological knowledge or inadequate facilities. As an alternative, using number-counting bags with straws might be an easier solution for teachers to practice and use in the learning process. The activity